Improving Power Supply Efficiency in Smart Grids Via Renewable Energy Adoption in Nigeria - Godspower Onyekachukwu Ekwueme (Barkah Publishing, 2026)
At the moment, Nigeria is experiencing great problems within its energy sector, which is evident from the state of the socio-economic lives of its people. However, there is great room for improvement through application of innovation. Adoption of smart grid systems within Nigeria’s energy sector will become imperative due to their ability to ensure efficient production, distribution, and consumption of energy in the future. The use of intelligent grids may be instrumental in overcoming persistent problems associated with poor supply of electricity, as well as reducing pressures on the national grid. Renewable energy systems, especially solar PV systems, are also innovative and sustainable energy production methods that can be adopted in Nigeria. Due to availability and reliability of solar energy, its adoption is likely to solve problems associated with grid instability and breakdowns. Notably, integration of smart energy solutions in Nigeria faces some key challenges